Treatment of Palm Oil Mill Effluent by Electrocoagulation with Presence of Hydrogen Peroxide as Oxidizing Agent and Polialuminum Chloride as Coagulant-Aid - Mohd, Nasrullah; Singh, Lakhveer; Zahari, Mohamad; Siti, Norsita; Santhana, Krishnan; Norul Wahida, Kamaruzaman; Zularisam, A. W. (Elsevier Ltd, 2017)
The purposes of this study were to investigate the effects of operating parameters, such as electrode material, current density, percentage of hydrogen peroxide and amount of polialuminum chloride (PAC) on chemical oxygen demand (COD) removal of palm oil mill effluent (POME). The current density was varied between 30–80 mA cm−2, PAC (1–3 g L−1) as coagulant-aid and 1 and 2% of hydrogen peroxide as an oxidizing agent. As for the performance of electrode type, iron was more effective than aluminum. It appeared that the removal of COD increased with the increased of current density. When PAC and H2O2 increased, the percent of COD removal was increasing as well. The overall results demonstrate that electrocoagulation is very efficient and able to achieve more than 70% COD removal in 180 min at current density 30–80 mA cm−2 reliant upon the concentration of H2O2 and PAC.